Relief: Observations on Creative Nonfiction as Pedagogy (LEARNing Landscapes, 2019)
“Relief: Observations on Creative Nonfiction as Pedagogy” offers a case study in the possibilities of using creative writing as a pedagogical tool with ESL students. Analyzing the experience, comments, and creative work of a Chinese nursing student named Wei Wan at Ryerson University, the essay explores the benefits of personal writing and peer workshops as tools for self-exploration, aesthetic appreciation, and confidence building. While urging teachers to see the advantages of this methodology, the paper also reflects on the literary values of creative work in hybrid, non-standard English forms.
Keywords: creative writing; creative nonfiction; defamiliarization; ESL/EFL teaching/writing; nonstandard English; personal essay; writing development